Targeting pyroptosis in periodontitis: mechanisms and therapeutic strategies - Qie, Yusen; Li, Jiaxin; Xu, Yang; Liu, Sijia; Liu, Na; Liu, Qing (Frontiers in Immunology, 2026)
Periodontitis is a common chronic inflammatory disease of the oral cavity. It is characterized by progressive destruction of the periodontal supporting tissues and alveolar bone loss, and it remains a leading cause of tooth loss in adults. In recent years, pyroptosis, a pro-inflammatory form of programmed cell death, has attracted increasing attention for its role in the initiation and progression of periodontitis. This review summarizes the molecular mechanisms and signaling pathways of pyroptosis. We highlight pyroptosis-targeted therapeutic strategies for periodontitis, including molecular targeted interventions, gene regulation, ion channel blockers, and natural compounds, among others. We also discuss major challenges and translational prospects in light of recent advances. This review aims to provide direction and guidance for developing novel periodontal therapeutic and regenerative strategies by targeting pyroptosis.